2012
DOI: 10.5424/sjar/2012103-462-11
|View full text |Cite
|
Sign up to set email alerts
|

La eficiencia productiva de la agricultura ecológica: el caso del sector de la uva en Cataluña

Abstract: Knowledge about productivity and efficiency differences between conventional and organic farms has important implications for the evaluation of the economic viability of these two agricultural practices. The main purpose of this study was to compare the efficiency ratings of organic and conventional grape farms in Catalonia. To do so, we fit a stochastic production frontier to cross sectional, farm-level data collected from a sample of 141 Catalan farms that specialize in grape growing. Results show that organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 26 publications
4
30
0
1
Order By: Relevance
“…Return on equity in Czech organic farms in 2001 was slightly lower than in conventional farms, but in 2005, the value of this index was similar for both farm groups and was only slightly above 10% (Redlichova 2007). Other studies indicate that economic results of organic farms are more favourable than the conventional farms (Brožová 2011;Guesmi et al 2012;Patil et al 2014). But it should be taken into account that economic results depend on the type of farms (Franckes, Latacz-Lohmann 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Return on equity in Czech organic farms in 2001 was slightly lower than in conventional farms, but in 2005, the value of this index was similar for both farm groups and was only slightly above 10% (Redlichova 2007). Other studies indicate that economic results of organic farms are more favourable than the conventional farms (Brožová 2011;Guesmi et al 2012;Patil et al 2014). But it should be taken into account that economic results depend on the type of farms (Franckes, Latacz-Lohmann 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This method of production first of all presents a chance of development for the poorer farms, provides management of surplus labour and improves the food supply in the local market, support economic development in rural communities (O'Hara, Parsons 2013). Organic farms are the object of study of many authors; however, most papers are focused on comparative analysis of production and economic results against the background of conventional farms (Lansink et al 2002;Redlichova 2007;Offerman et al 2009;Gardebroek et al 2010;Nachtman 2010;Brožová 2011;Guesmi et al 2012;Patil et al 2014). The author of this article also conducted these types of studies (Koloszko-Chomentowska 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Five studies indicate a higher production elasticity of labour on organic than conventional farms [8,9,19,23,32], whereas five other studies found a lower value of elasticity on organic farms [15,16,20,21,28]. This might seem to be somewhat counterintuitive, given that organic farming is traditionally thought to be more labour-intensive than conventional farming, and we would expect output to be more sensitive to changes in labour on organic than conventional farms.…”
Section: Labour Use and Technical Efficiencymentioning
confidence: 92%
“…Overall we found only six studies [8][9][10][11][12][13] comparing labour use per hectare or head of livestock on organic and conventional farms that include a breakdown by farm type. These studies suggest that labour use depends on farm structure, in particular farm type and size.…”
Section: Labour Use and Farm Structurementioning
confidence: 99%
See 1 more Smart Citation